Comparison of Characteristics and Survival of New-Onset Hepatocellular Carcinomas With or Without Cirrhosis in a Tertiary Center - Araz, Filiz; Soydaş, Barış; Özer, Birol; Karadeli, Elif; Erbay, Gürcan (Turkish Journal of Gastroenterology, 2024)
Background/Aims: Although hepatocellular carcinoma (HCC) usually develops in cirrhotic livers, HCCs could also arise in non-cirrhotic livers. We aimed to compare the characteristics and survival of cirrhotic- and non-cirrhotic HCCs. Materials and Methods: Data of HCC patients between 2011 and 2021 in a single tertiary center was evaluated retrospectively. Demographic, clinical, laboratory, tumoral and pathological features, and survival outcomes of cirrhotic and non-cirrhotic HCCs were compared. Results: The study included 188 HCC patients. Median age was 64 (26-92) years and similar for study groups (P = .208). Both groups had similar male/female ratio. Forty-two patients (22.3%) had HCC in non-cirrhotic liver. Non-cirrhotic HCCs had similar tumor differentiation type, radiological characteristics, Milan, University of California San Francisco, and the Barcelona Clinic Liver Cancer stages, but more unifocal lesion (78.6% vs. 59.6%) and larger tumor size (89.5 (16-240) mm vs. 59.0 (12-290) mm) at presentation compared to non-cirrhotic HCCs. Despite larger tumor size, non-cirrhotic HCC patients had better overall, disease-free and progression-free survival rates than cirrhotic HCCs. Overall survivals for 1 and 3 years were 71.4% and 49.7% for non-cirrhotic and 54% and 28.3% for cirrhotic HCCs, respectively (P = .035). According to Cox analyses, Eastern Cooperative Oncology Group score (P < .001, hazards ratio (HR): 4.05) and curative treatments (P < .001, HR: 0.21) were predictive for overall survival in cirrhotic HCCs. Curative treatment (P = .027, HR: 0.31) was found to be a significant predictor for overall survival in non-cirrhotic HCCs. Vascular invasion was the only independent predictor for disease-free survival (HR: 2.62, 95% CI 1.01-6.93, P = .049) for non-cirrhotic HCCs. Conclusion: Despite larger tumor size and similar tumor stages, compared to cirrhotic HCCs, non-cirrhotic HCCs were associated with better survival outcomes. Cite this article as: Araz F, Soydaş B, Özer B, Karadeli E, Erbay G. Comparison of characteristics and survival of new-onset hepatocellular carcinomas with or without cirrhosis in a tertiary center. Turk J Gastroenterol. 2024;35(7):539-550.